The Effectiveness of Shadowing Technique on students Listening abilities at SMPN 2 Galesong Utara - Nur Imam imam; Sukardi Weda; Abd Halim (International Journal of Language, Education, and Literature, 2025)
This study investigates the impact of using the Shadowing approach to teach listening in a junior high school. Data was collectedusing a qualitative study approach, including pre-tests, treatment and post-tests. The study aims to answer key questions: what influence the shadowing approach has on seventh-grade students' listening skills, and how the shadowing technique affects EFL learners' listening cognitive processes. The data show shadowing can help students improve their listening. According to the study's results, students in the experimental class improve in their scores after experiencing Shadowing technique. While thecontrol class the result showed that students listening abilities had decreased. The shadowing method increased students' listening skills in a variety of ways, including attentiveness, active participation, and resource usage. The shadowing method helped students enhance their attention and refocusing abilities, as well as their use of pronunciation and intonation to facilitate comprehension. These benefits demonstrate that shadowing is effective to improve students' interest and active listening skills.